Long-term Outcomes Following Vickers Ligament Release and Growth Modulation for the Treatment of Madelung Deformity. Issue 4 (April 2020) - Del Core, Michael; Beckwith, Terri; Phillips, Lee; Ezaki, Marybeth; Stutz, Chris; Oishi, Scott N.
Abstract : Background: Madelung deformity arises from a partial distal radial growth disturbance in combination with an abnormal hypertrophic ligament spanning the volar radius and carpus, termed, the Vickers ligament. The purpose of this study is to report long-term clinical and radiographic outcomes following Vickers ligament release and distal radial physiolysis in a population of skeletally immature patients with symptomatic Madelung deformity. Methods: Medical records were retrospectively reviewed of patients with Madelung deformity surgically treated between 1994 and 2005. All eligible patients who underwent a Vickers ligament release and distal radial physiolysis were contacted and invited to return to the clinic for follow-up. Results: Six patients (8 wrists) with Madelung deformity underwent Vickers ligament release and distal radial physiolysis. All were white females with a mean age at initial presentation of 11.4 years (10 to 12.8 y). Mean age at the time of initial surgery was 12.0 years (10.0 to 14.5 y). The median follow-up time was 10.6 years (5.8 to 21.9 y) and the average age at last follow-up was 23.1 years (17.5 to 32.2 y). Pain alone or in combination with concerns for deformity was the chief complaint in 6 of 8 of the wrists. At 1 year of clinical follow-up, 7 of 8 wrists were reported to be pain-free, and 6 of the 8 were noted to be completely pain-free at last follow-up. Motion in flexion, extension, pronation, supination, radial, or ulnar deviation was similar between the preoperative status and long-term follow-up. The average preoperative ulnar tilt was 35.1 degrees (SD: 8.5 degrees), average preoperative lunate subsidence was 1.9 degrees (SD: 1.8 degrees), and average preoperative palmar carpal displacement was 21.9 degrees (SD: 2.9 degrees). At the final follow-up, there was a large progression in lunate subsidence, but minimal change in ulnar tilt and palmar carpal displacement. At last clinical follow-up, 2 of the 6 patients had undergone a subsequent procedure including 1 radial dome osteotomy and 1 ulnar shortening osteotomy. Conclusion: In the skeletally immature patient population with Madelung deformity with growth potential remaining, distal radial physiolysis and Vickers ligament release is associated with relief of pain, preservation of motion, and, a reasonable rate of reoperation. Type of Study: This was a therapeutic study. Level of Evidence: Level II. Abstract : Supplemental Digital Content is available in the text.